Pembaharuan Hukum Tata Negara Indonesia Dalam Rangka Mewujudkan Cita Negara Hukum Nasional - titik triwulan tutik (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2018)
Legal products or legislation as objects of Constitutional Law contain elements of dynamics that are closely related to the movements and needs of individuals in society and the growth of state organizations. Considering the interrelation between Constitutional Law and social changes, it is obvious that what is important in Constitutional Law is not just studying the Constitution and legislation, but more pressure should be given to the process of the Act. In this context, awareness and renewal of ways of thinking in the field of Constitutional Law are needed so that the legal narrowness caused by the lack of extensive legal treasury no longer appears in the form of legal thinking or mere juridisch denken, which results in a narrow mindset in the form of imitating the rules. rules only. Constitutional law not only pays attention to a formal perspective, but also a functional angle, so that it will always be dynamic.